A low cost virtual reality system for home based rehabilitation of the arm following stroke: a randomised controlled feasibility trial - Standen, Penny; Threapleton, K.; Richardson, A.; Connell, L.; Brown, D.J.; Battersby, S.; Platts, F.; Burton, Audrey (SAGE Journals, 2017)
OBJECTIVE: To assess the feasibility of conducting a randomised controlled trial of a home-based virtual reality system for rehabilitation of the arm following stroke. DESIGN: Two group feasibility randomised controlled trial of intervention versus usual care. SETTING: Patients' homes. PARTICIPANTS: Patients aged 18 or over, with residual arm dysfunction following stroke and no longer receiving any other intensive rehabilitation. INTERVENTIONS: Eight weeks' use of a low cost home-based virtual reality system employing infra-red capture to translate the position of the hand into game play or usual care. MAIN MEASURES: The primary objective was to collect information on the feasibility of a trial, including recruitment, collection of outcome measures and staff support required. Patients were assessed at three time points using the Wolf Motor Function Test, Nine-Hole Peg Test, Motor Activity Log and Nottingham Extended Activities of Daily Living. RESULTS: Over 15 months only 47 people were referred to the team. Twenty seven were randomised and 18 (67%) of those completed final outcome measures. Sample size calculation based on data from the Wolf Motor Function Test indicated a requirement for 38 per group. There was a significantly greater change from baseline in the intervention group on midpoint Wolf Grip strength and two subscales of the final Motor Activity Log. Training in the use of the equipment took a median of 230 minutes per patient. CONCLUSIONS: To achieve the required sample size, a definitive home-based trial would require additional strategies to boost recruitment rates and adequate resources for patient support.